Lifestyle As a Factor for Overweight in Adolescents: Lifestyle sebagai Faktor Risiko Overweight Remaja - Pradigdo, Siti Fatimah; Nugraheni, Sri Achadi; Putri, Rezkia Nadia (Universitas Airlangga, 2023)
Background: Overweight prevalence in Indonesia is 16.5% in late teens. Lifestyle is a risk factor for overweight teenagers, especially those who live in urban areas. Objectives: To analyze the relationship between lifestyle and eating patterns on the incidence of overweight in teenagers living in urban areas. Methods: This research was an observational study with a cross-sectional design. The population of teenagers in Jakarta aged 15 - 18 was 996, based on Ministry of Health Basic Health Research 2018 data. The sample number were 372 using the research criteria of simple random sampling. Research instruments include questionnaires, digital weight scales, and stadiometers. The statistical test used Chi Square to determine the risk factors for overweight. Results: The number of overweight teenagers was 0.12%; the majority were in their late teens (55.6%), female (52.7%), rarely consumed sweet foods (62.9%), often consumed sweet drinks (58.9%), rarely consume fatty/fried foods (61.0%), often consume vegetables and fruit (65.1%), do not drink alcohol (98.4%), moderate sport activity (41.9%), and not smoking (77.7%). Overweight risk factors are consuming sweet drinks (p=0.044; OR=1.582; CI=1.010-2.477) and education (p=0.040; OR=1.847; CI=1.059 – 3.220). Adolescents with frequent sweet drinks consumption have a 1.58 risk of being overweight compared to those who do not consume sweet drinks. Adolescents with higher education are at risk of being overweight by 1.84 compared to those with lower education. Conclusions: Risk factors for overweight Jakarta teenagers are frequent consumption of sweet drinks and advanced education.